Validation of the General Medication Adherence Scale in Pakistani Patients With Rheumatoid Arthritis - Naqvi, Atta Abbas; Hassali, Mohamed Azmi; Rizvi, Mehwish; Zehra, Ale; Nisa, Zeb-un-; Islam, Md. Ashraful; Iqbal, Muhammad Shahid; Farooqui, Maryam; Imam, Mohammad Tarique; Hossain, Mohammad Akbar; Khan, Irfanullah; Iqbal, Muhammad Zahid; et al. (Frontiers in Pharmacology, 2020)
Objective The aim was to validate the Urdu version of General Medication Adherence Scale (GMAS) in patients with rheumatoid arthritis disease. Methods A 2-month (March – April 2019) cross-sectional study was conducted in randomly selected out-patients with rheumatoid arthritis. The sample size was calculated using item-subject ratio of 1:20. The scale was evaluated for factorial, construct, concurrent and known group validities. Construct validity was established by correlating scores of EQ-5D quality of life scale and GMAS adherence score. Concurrent validity was established by correlating the GMAS adherence score with pill count. Analyses for sensitivity were also conducted. Cut-off value was determined through receiver operator curve (ROC), and test-retest method was used to analyze internal consistency and reliability. Data were analyzed through IBM SPSS, IBM AMOS and MedCalc. The Urdu version of EQ-5D quality of life questionnaire was used with permission from developers (#ID20884). The study was approved by an ethics committee (#NOV:15).. Results A total of 351 responses were analyzed. The response rate was 98%. Reliability was in acceptable range, i.e., Cronbach α = 0.79. Factorial validity was established by calculation of satisfactory fit indices. Correlation coefficients for construct and concurrent validities were ρ = 0.663, p<0.01 and ρ = 0.747, p<0.01, respectively. Known group validity was established as significant association of adherence score with, insurance (p<0.02) and, illness duration (p<0.01), were reported. Sensitivity of the scale was 94%. Most patients had high adherence (N = 159, 45.3%). Conclusion The Urdu version of GMAS demonstrated adequate internal consistency and was validated. These results indicate that it is an appropriate tool to measure medication adherence in Pakistani patients with rheumatoid arthritis.